Socjalizacja polityczna w przebiegu życia – perspektywa kontynuacji i zmiany - Hildebrandt-Wypych, Dobrochna (Studia Edukacyjne, 2020)
The following text presents various alternative theoretical approaches in political socialization research. Some of the theoretical insights provided by the functional, systemic and interpretative perspectives are identifiedin order to depict the discussion around the continuity and change within the political socialization research. Whereas in the firstperiod of political socialization research the aim was to explain the continuity in the development of political orientations, it was later forced to account for modificationand the potential for change (especially when addressing the interpretative issues of identity politics). After describing the field’stheoretical shifts, the life-course model of political socialization is presented. The life-course model attempts to deal with the problem of continuity and change in the political socialization process, pointing to its remarkable complexity and lifelong flexibility.It offers a systematic, interdisciplinary and holistic way of conceptualizing political socialization. It points to the importance of political socialization research in demonstrating interdependence between objective functions of the political system and subjective political learning of a reflexive individual.